1999
DOI: 10.1007/s004649901124
|View full text |Cite
|
Sign up to set email alerts
|

Nerve irritation after laparoscopic hernia repair

Abstract: Reduction in the number of clips used and careful attention to the anatomic nerve course during preparation and placement of mesh led to a significant reduction in the occurrence of nerve irritations. In the last 100 patients who underwent laparoscopic hernia repair, only one nerve lesion was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 20 publications
0
70
0
1
Order By: Relevance
“…A meta-analysis conducted by Kaul et al [10] of 662 hernia repairs where in 394 mesh were fixed with tacks while in 268 mesh were fixed with fibrin glue found that incidence of pain was significantly higher in the tacker group. Stark et al [23] reported incidence of pain in 4.2 % of patients. Tolver et al [15] reported that day 1 scores and all cumulated scores of pain during rest, discomfort, and fatigue were significantly lower in the fibrin group compared with the tacker group (all p values ≤0.02)…”
Section: Groin Pain and Orchitismentioning
confidence: 97%
“…A meta-analysis conducted by Kaul et al [10] of 662 hernia repairs where in 394 mesh were fixed with tacks while in 268 mesh were fixed with fibrin glue found that incidence of pain was significantly higher in the tacker group. Stark et al [23] reported incidence of pain in 4.2 % of patients. Tolver et al [15] reported that day 1 scores and all cumulated scores of pain during rest, discomfort, and fatigue were significantly lower in the fibrin group compared with the tacker group (all p values ≤0.02)…”
Section: Groin Pain and Orchitismentioning
confidence: 97%
“…Additionally, placement of staples in close proximity to the inguinal ligament (IL) during abdominal hernia repair (Eubanks, 2003) has resulted in compression of the LFCN and subsequent symptomatology associated with MP. Specifically, since the advent of laparoscopic hernia repair it has been reported that the incidence of iatrogenic MP has increased fivefold from 1 to 5% over open surgical procedures (Stark, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The nerve then pierces the Obliquus internus (distributing filaments to it) just medial to the anterior superior iliac spine, at this point it becomes visible between the external and internal obliques and then it passes into the inguinal canal, accompanying the spermatic cord, through the subcutaneous inguinal ring. [3][4][5] After leaving the superficial inguinal ring, the ilioinguinal nerve subdivides into:…”
Section: Discussionmentioning
confidence: 99%